2015
DOI: 10.1016/j.jagp.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Working Memory in Geriatric Depression: An fMRI Study

Abstract: Cognitive dysfunction in geriatric depression may be related to reorganization of brain networks involved in working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…One implication of these findings is that concomitant targeting of reduced motivation may be a more effective means of developing self-regulation of memory impairments in PD. Such an approach could be especially useful in those with depression (Goedeken, Potempa, Prager, & Foster, 2018) given that our findings confirmed that increased depressive symptomatology was associated with impairments of both objective and subjective memory (e.g., Dumas & Newhouse, 2015;Fastame, 2014). However, additional research in this area is needed since prior research indicates that apathy and depression are not correlated in PD (Pluck & Brown, 2002).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…One implication of these findings is that concomitant targeting of reduced motivation may be a more effective means of developing self-regulation of memory impairments in PD. Such an approach could be especially useful in those with depression (Goedeken, Potempa, Prager, & Foster, 2018) given that our findings confirmed that increased depressive symptomatology was associated with impairments of both objective and subjective memory (e.g., Dumas & Newhouse, 2015;Fastame, 2014). However, additional research in this area is needed since prior research indicates that apathy and depression are not correlated in PD (Pluck & Brown, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…While increased clarity concerning the impact of PD on objective and subjective memory and the relationship between them is highly desirable, such a goal is complicated by confounding variance in depressive symptomatology (Dumas & Newhouse, 2015;Fastame, 2014). This is rarely considered in PD samples and, when it has, findings have been mixed (Coutler, 1989;Reynolds, Hanna, Neargarder, & Cronin-Golomb, 2017;Sitek et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported aberrant EEG performance, such as increased slow activity in the frontal areas (Grin-Yatsenko et al, 2009 , 2010 ), in depressed patients. Depressed older adults were found to have decreased frontal and parietal activation during some working memory tasks (Dumas and Newhouse, 2015 ). Weakened prefrontal and frontal connections may suggest decreased activation of the cortico-limbic circuit, which is related to symptoms such anhedonia or blunted affect (Fingelkurts and Fingelkurts, 2006 ).…”
Section: Discussionmentioning
confidence: 99%